2021
DOI: 10.1111/aos.14893
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor inhibitors for predominantly Caucasian myopic choroidal neovascularization: 2‐year treatment outcomes in clinical practice: data from the Fight Retinal Blindness! Registry

Abstract: Purpose: To report the 24-month outcomes of vascular endothelial growth factor (VEGF) inhibitors for myopic choroidal neovascularization (mCNV) in predominantly Caucasian eyes in routine clinical practice. Methods: Retrospective analysis of treatment-na€ ıve eyes starting intravitreal injection of VEGF inhibitors of either bevacizumab (1.25 mg) or ranibizumab (0.5 mg) for mCNV from 1 January 2006 to 31 May 2018 that were tracked in the Fight Retinal Blindness! registry. Results: We identified 203 eyes (bevaciz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Indeed, the risk of visual loss increased by 22% for each decade increase in age, regardless of the baseline BCVA and peak vision score. Previous authors 24 highlighted the association between older age and worse visual prognosis in mMNV eyes undergoing anti-VEGF treatment. We do not have data on the duration of mMNV, but older age may suggest long-standing neovascular lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the risk of visual loss increased by 22% for each decade increase in age, regardless of the baseline BCVA and peak vision score. Previous authors 24 highlighted the association between older age and worse visual prognosis in mMNV eyes undergoing anti-VEGF treatment. We do not have data on the duration of mMNV, but older age may suggest long-standing neovascular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The reported rate of mMNV recurrences ranges between 23% and 62%. 17,[24][25][26] In this study, we estimated a global recurrence rate of 53% and a cumulative risk of three events by the ninth year. Our and previous data showed that recurrences have negative consequences on visual outcomes, accelerating visual loss.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, elderly patients with myopia might experience more significant tissue damage resulting from myopic degeneration, as indicated by the characteristics observed in our patient population. The documented recurrence rate of mMNV varies between 23% and 62% 20–24…”
Section: Discussionmentioning
confidence: 99%
“…The documented recurrence rate of mMNV varies between 23% and 62%. [20][21][22][23][24] Collectively, these three studies provide valuable insights into the factors linked with recurrence in patients with m-CNV. The study by Jain et al 17 highlighted the number of injections received as a significant predictor of recurrence, emphasising the importance of appropriate treatment strategies and follow-up care.…”
Section: Discussionmentioning
confidence: 99%
“…More than 1.2 million anti-VEGF IVTs were administered in France in 2020 [2]. Besides age-related macular degeneration (AMD), anti-VEGF agents are used for other indications-notably, in proliferative diabetic retinopathy [3], diabetic macular edema (DME) [4], retinal vein occlusion (RVO) [5], myopic choroidal neovascularization [6], inflammatory macular edema, inflammatory choroidopathy, and radiation maculopathy [7]. These retinal diseases may affect young people and therefore women of childbearing age.…”
Section: Introductionmentioning
confidence: 99%